The Effect of Using Puzzle Media on Arabic Vocabulary Mastery Among Fourth-Grade Students at Kuttab An-Nahl Islamic Elementary School, Danjung-Danjung - Silvia, Maisa; Yusra, Oktarina (Program Studi Pendidikan Bahasa Arab Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2026)
The main problem in teaching Arabic are that method used are still traditional making the learning process less interactive. However, studies examining the effectiveness of puzzle-based learning media for improving Arabic vocabulary mastery at the elementary Islamic school level remain limited. Students struggle to memorize new vocabulary and use it in context. Furthermore, some do not participate actively during lessons and engage in side activities because the methods used do not suit their interest. This thesis aims to determine the effect of using puzzles on mastering Arabic Vocabulary among fourth-grade students at elementary school Kuttab An Nahl Dangung-Dangung. This study employed a quasi-experimental design using a pretest-posttest control group design. The data collection method was observation and testing, and the research was analyzed using the independent-t, normality test, and homogenety test. The result showed that the average score of the experimental group after applying the method was 95, while the average score of the control group was 75. The independent samples t-test showed a significant difference between the two groups (t = 3.501, p < 0.05) was greater than the value in the table (1,812), which confirms the effectiveness of using the puzzle method in improving mastery of Arabic Vocabulary in the fourth-grade students at elementary school Kuttab An Nahl Dangung-Dangung.